Policy Synergy between The Provincial Government of East Java and The Central Government on Health Quarantine in The Treatment of Covid-19 - Purba, Iman Pasu Marganda Hardianto; Suwanda, I Made; Adi, Agus Satmoko; Wijaya, Rahmanu (Department of Public Administration, Universitas Negeri Surabaya, 2021)
ABSTRACTThis study aims to examine the policy synergy between the Provincial Government of East Java and the Central Government in dealing with Covid-19. The urgency of this study is to explain to what extent policies between the Local Governments and the Central Government are in sync. This research uses legal research methods. Primary data includes statutory regulations, especially the Law on Health quarantine and secondary data such as previous research, expert opinion, and other relevant document data. This study concludes that the East Java Provincial Government and the Central Government have a synergy in dealing with Covid-19 in Indonesia. However, neither the legal products that are produced nor policies that are political in nature do not conflict with one another.Â Â ABSTRAKPenelitian ini bertujuan untuk mengkaji sinergitas kebijakan antara Pemerintah Provinsi Jawa Timur dengan Pemerintah Pusat dan dalam menghadapi Covid-19. Urgensi penelitian ini adalah menjelaskan sejauhmana kebijakan antara Pemerintah Pusat dan Pemerintah Daerah sinkron. Penelitian ini menggunakan metode penelitian hukum. Data primer mencakup peraturan perundang-undangan terutama Undang-undang tentang karantina Kesehatan dan data sekunder seperti penelitian terdahulu, pendapat para pakar, dan data dokumen lain yang relevan. Kajian ini menyimpulkan bahwa Pemerintah Provinsi Jawa Timur maupun Pemerintah Pusat memiliki sinergi dalam menangani Covid-19 di Indonesia. Baik produk hukum yang dihasilkan maupun kebijakan yang bersifat politis, tidak bertentangan satu sama lain.Â